STRATEGI KONTEN STORYTELLING TIKTOK UNTUK MENINGKATKAN ENGAGEMENT AUDIENS @KILIKILIADVENTURE - Ahmad Dzakwan At-Taqy; Amiruddin Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of the TikTok platform has transformed the digital marketing landscape, particularly within the highly competitive tourism industry. This study aims to analyze the storytelling content strategy on TikTok to increase audience engagement on the @KiliKiliAdventure account. This study employed a descriptive qualitative approach combined with a digital metrics analysis using the Engagement Rate by Reach (ERR) formula. The scope of research objects was limited to TikTok video content produced and uploaded over a three-month period (February–April 2026). Data collection techniques included participant observation, in-depth interviews with the marketing team, and digital analytical documentation. The results indicate that storytelling-based content utilizing seasonal marketing momentum and listicle hook techniques without direct commercial Call to Action (subtle branding) successfully penetrated the FYP (For You Page) algorithm, achieving a peak performance of 43,000 views. Conversely, direct promotional content (hard-selling) faced high ad aversion from the audience, causing the algorithm to stall its distribution. Operationally, the implementation of a 5-day agile workflow management proved to be the primary key to maintaining the consistency and quality of multimodal messages on TikTok.